Transcriptome analysis provides insights into the cell wall and aluminum toxicity related to rusty root syndrome of Panax ginseng - Tong, Aizi; Liu, Wei; Wang, Haijiao; Liu, Xiaoliang; Xia, Guangqing; Zhu, Junyi (Frontiers in Plant Science, 2023)
Rusty root syndrome is a common and serious disease in the process of Panax ginseng cultivation. This disease greatly decreases the production and quality of P. ginseng and causes a severe threat to the healthy development of the ginseng industry. However, its pathogenic mechanism remains unclear. In this study, Illumina high-throughput sequencing (RNA-seq) technology was used for comparative transcriptome analysis of healthy and rusty root-affected ginseng. The roots of rusty ginseng showed 672 upregulated genes and 526 downregulated genes compared with the healthy ginseng roots. There were significant differences in the expression of genes involved in the biosynthesis of secondary metabolites, plant hormone signal transduction, and plant–pathogen interaction. Further analysis showed that the cell wall synthesis and modification of ginseng has a strong response to rusty root syndrome. Furthermore, the rusty ginseng increased aluminum tolerance by inhibiting Al entering cells through external chelating Al and cell wall-binding Al. The present study establishes a molecular model of the ginseng response to rusty roots. Our findings provide new insights into the occurrence of rusty root syndrome, which will reveal the underlying molecular mechanisms of ginseng response to this disease.